Evaluation of a Preventative Health Consultation Service for Patients at Student-Run Walk-In Health Clinics - Jessica Stickel; Susan Ngo; Akshara Kumar; Laura Rhodes; Jacqueline Zeeman (Journal of Student-Run Clinics, 2021)
Background: Preventative health services are often underutilized by under-resourced populations. This study aimed to evaluate the utility of a student-run preventative health consultation (PHC) service at free walk-in clinics.Methods: This prospective cohort study recruited adult participants from student-run free walk-in clinics at a Spanish-language church and a homeless shelter. During the PHCs, recommendations from the United States Preventative Services Task Force and Centers for Disease Control and Prevention immunization schedule were discussed with participants. The top three recommendations for each participant were prioritized using shared decision-making. Participants completed a post-PHC survey and were contacted within three months about recommendation completion status. Recommendations were grouped into categories and analyzed using descriptive statistics.Results: Of the 29 people enrolled in the study, 48% (n=14) were Spanish-speaking, and 45% (n=13) were homeless/displaced. There were 87 recommendations made and categorized as health behaviors (29.9%, n=26), vaccinations (18.4%, n=16), chronic disease screenings (18.4%, n=16), communicable disease screenings (17.2%, n=15), cancer screenings (11.5%, n=10), and other (4.6%, n=4). The most common completed recommendations were changes in health behaviors (46.2%, n=12) and chronic disease screenings (37.5%, n=6). Of the participants who completed the post-PHC survey, 96% (n=27) agreed or strongly agreed they learned new information about their health from the PHC, and 100% (n=29) reported being glad to have engaged in the PHC and that the PHC service should continue at the monthly clinics.Conclusions: Health behaviors, vaccinations, and chronic disease screenings were the most frequently prioritized preventative health needs. Student-run PHC services may offer a way to increase underserved patient knowledge and engagement with preventative healthcare.